Influence of Assessment Practices on Business Education Students' Academic Performance in Nigerian Colleges of Education - Ademiluyi, Lawrence F; Akinlabi, David A (Journal of Education and Practice, 2022)
Purpose: Serious complaints from lecturers and students concerning lackadaisical approach to assessment informed the decision of the researchers to examine the influence of assessment practices on business education students' academic performance in colleges of education in Southwest Nigeria. Two purposes, two research questions and two null hypotheses guided the study. Methodology: The study adopted the descriptive survey research design while the population of the study consisted of 200 business education lecturers and 2000 Nigeria Certificate in Education (NCE) final year regular students registered for the 2020/2021 academic session. The sample comprised 132 lecturers as well as 322 students. The multi-stage sampling technique incorporating purposive sampling and simple random sampling techniques were used to select the sample for the study. The instruments for data collection Students Academic Performance Proforma (SAPP) coupled with lecturers and students questionnaires titled; Influence of Assessment Practices on Business Education Students' Academic Performance Questionnaire (IAPBESAPQ). The Cronbach Alpha formula was used to establish the internal consistency reliability coefficients of 0.77 for lecturers' questionnaire and 0.78 for students' questionnaire. The data collected were analyzed using frequency tables, mean, standard deviation, t-test statistics and linear regression analysis. Findings: The study found that, end of semester examination (ESE) (Mean = 4.00, SD = 0.61), written tests (Mean = 3.93, SD = 0.45) classroom exercises (Mean = 3.73, SD = 0.44) and take-home assignment (Mean = 3.60, SD = 0.53) are the most commonly adopted assessment practices by business education lecturers in colleges of education. It was also revealed that assessment practices have significant influence on academic performance (F (1.452) = 1.609, p = 0.205) of business education students in colleges of education. Unique Contribution to Theory, Policy and Practice: Finally, it was recommended among others that business education lecturers in colleges of education should adopt assessment practices that elicit autonomy, engagement, high-order thinking and increased proficiency in skill courses. As a contribution to theory, practice and policy, this study exposed an urgent need for a paradigm shift from traditional assessment practices to competency-based assessment practices which are essential ingredients for survival and advancement in this era of globalization.